Mastigação: avaliação com dois diferentes instrumentos - Barros, Thaynã Aguiar (2016)
ntroduction: Chewing is considered one of the most important functions in the Stomatognathic System. Patients rarely come to a speech language pathologist with chewing-related complains and through a detailed evaluation it is possible to have a precise diagnosis. In the chewing evaluation we have to acknowledge several steps such as: food grasping, mouth closure while chewing bolus, vertical and lateral jaw movements, rhythm, speed, among other aspects, especially the kind of food used in evaluation. In the orofacial motricity field there are various assessment tools, however two of them emerge for being used frequently in therapy and in researches. Purpose: to compare the chewing evaluation findings in a teenager group according to the Expanded protocol of orofacial myofunctional evaluation (OMES-E) protocol and the Orofacial myofunctional evaluation – Marchesan, Barretin-Felix, Genaro, Rehder (MBGR). Methods: the sample was composed of 46 teenagers, 30 female and 16 male, between 11 and 16 years old, and the average age was 14.8 years. The assessment tools were used only the part referring to chewing. A wafer cookie was used for the OMES-E protocol and a roll was chosen for the MBGR. Moreover, the chewing times were analyzed for each assessment tool. The collected data from both evaluation tools were submitted to the comparative statistical analysis. Results: the evaluation tools have been shown similar to assess chewing, although they had inverted punctuations comparing to the normal parameters. The item “others” on the OMES-E corresponded to the uncoordinated jaw movements, head movements or movements from other parts of the body, inadequate posture, and food escape. On the MBGR this same item corresponded to lips closure, speed, noisy chewing, and nonintended muscular contractions; and those results showed a statistical significance. The data has also shown differences related to chewing time. Chewing a roll took almost double the time comparing to a wafer cookie. Conclusion: comparing the chewing of the teenage group studied according to the OMES-E and the MBGR, in the aspects such as bite, and type and way, they responded similarly, although they responded differently in other chewing aspects such as: posture, jaw movements, food escape, lips closure, speed, noise, muscular contraction, and time. In comparison, the roll took almost double the time comparing to the wafer cookie although it did not change the biting pattern or the type and way of chewing overall according to both evaluation protocols